All things being equal? Longitudinal patterns of mental disorder symptoms and associations with key social determinants in a large cohort of Australian adolescents - Scarlett Smout; Nicola C. Newton; Siobhan O’Dean; Katrina E. Champion; Lauren A. Gardner (Australian and New Zealand Journal of Public Health)
Objective: Using longitudinal data from a large cohort of Australian adolescents, this study examines the following: 1) changes in depression, psychological distress and anxiety symptoms, 2) associations between symptoms and social determinants (gender, cultural/linguistic diversity, family affluence, school socio-educational advantage, and geographic remoteness), and 3) interactions between social determinants and effects on symptoms. Methods: Students from 71 Australian schools completed annual surveys from Year 7 (2019, n=6,639, Mage:12.7) to 10. Generalised linear mixed effects regression analyses examined associations between social determinants and mental disorder symptoms. Results: Mean mental disorder symptom scores increased over time, with cisgender females and gender diverse participants experiencing heightened baseline symptoms and an increased growth in symptoms compared with cisgender males. Interaction effects suggest that females in the lowest affluence group experienced compounded adversity, with heightened anxiety and depressive symptoms over-and-above the effects of affluence or gender alone. Conclusions: Among this large cohort of Australian adolescents, elevated mental disorder symptoms were common and were associated with key social determinants. Implications for public health: This study highlights the need to address adolescent mental health in public health policy, research, and practice. Responses should proportionately target groups experiencing disproportionate burdens, including female and gender diverse adolescents; particularly those experiencing low affluence.